Antarctic lakes suggest millennial reorganizations of Southern Hemisphere atmospheric and oceanic circulation. - Hall, B; Denton, G; Fountain, A; Hendy, C; Henderson, G (2010)
The phasing of millennial-scale oscillations in Antarctica relative to those elsewhere in the world is important for discriminating among models for abrupt climate change, particularly those involving the Southern Ocean. However, records of millennial-scale variability from Antarctica dating to the last glacial maximum are rare and rely heavily on data from widely spaced ice cores, some of which show little variability through that time. Here, we present new data from closed-basin lakes in the Dry Valleys region of East Antarctica that show high-magnitude, high-frequency oscillations in surface level during the late Pleistocene synchronous with climate fluctuations elsewhere in the Southern Hemisphere. These data suggest a coherent Southern Hemisphere pattern of climate change on millennial time scales, at least in the Pacific sector, and indicate that any hypothesis concerning the origin of these events must account for synchronous changes in both high and temperate latitudes.